PERANCANGAN SISTEM INFORMASI RETRIBUSI BERBASIS WEB UNTUK OPTIMALISASI PENGELOLAAN KEUANGAN PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA DAERAH KOTA JAMBI - Cecilia Cecilia; Fadhliazis Fadhliazis; Abe Wisnu Syaputra; Arif Setiadi; Tri Rizqi Ariantoro; Akhmad Faisal Husni (Djtechno: Jurnal Teknologi Informasi, 2025)
This research aims to design a web-based retribution information system to optimize financial management at the Regional Civil Service and Human Resources Development Agency (BKPSDMD) of Jambi City. The current manual management of retribution often leads to problems such as data inaccuracy, reporting delays, and difficulties in monitoring. Therefore, an integrated and computerized information system is needed to improve the efficiency and transparency of retribution management. The system design methods used in this study include needs analysis, database design, user interface design, and system architecture design. The result of this research is a web-based retribution information system design that is expected to assist BKPSDMD Jambi City in optimizing financial management, improving accountability, and providing better services to the community.